Experimental assessment of the cyclic response of friction-based isolators under bidirectional motions. Issue 114 (November 2018) - Pavese, Alberto; Furinghetti, Marco; Casarotti, Chiara
Abstract: Experimental research on the lateral response of Concave Surface Sliders (CSS) under bi-directional earthquake excitations has shown significant differences in comparison to the uni-directional case. This is mainly due to the stepwise variation of the direction of the frictional force, which is assumed to be parallel to the device trajectory; on the other hand recentering force can still be considered as directed towards the centre of the device. The present endeavor shows results of a wide experimental campaign on a full-scale CSS device, according to a special testing protocol with both uni-directional and bi-directional dynamic tests. Results have shown non-negligible discrepancies in the hysteretic loops of the device between the bi-axial interaction of the directions of motion, in comparison to radial motions: such a behaviour is expected to significantly influence the overall response of a base-isolated structural system, if it is not properly modeled. Highlights: Bidirectional and unidirectional motions have same friction coefficient decay trend. Bidirectional motions lead to additional fluctuations of friction coefficient value. Expressions for average friction coefficient per bidirectional cycle are proposed. Bidirectional motions have same frictional decay regardless the trajectory shape.